2015
DOI: 10.1111/bij.12715
|View full text |Cite
|
Sign up to set email alerts
|

Induced expression of defence-related genes in barley is specific to aphid genotype

Abstract: Understanding the mechanisms by which plants respond to attack is of great ecological and economic importance. When phloem‐feeding insects feed they can influence the expression of defence‐related genes in the plant. While it is well‐documented that the genotype of the feeding insect can influence plant fitness traits, thus far the effect of insect genotype on the induction of defence‐related genes in the plant has had relatively little attention. To investigate the molecular specificity of plant–insect intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…in barley with monogenic resistance to S. graminum , pre-infestation with a non-compatible aphid biotype led to reduced feeding by a compatible biotype, indicating defense induction by the former (Hays et al, 1999). Similarly, Zytynska et al (2016) found biotype-dependant induction of numerous transcripts and reduction of aphid population growth of S. avenae in barley. In neither of these two barley studies were there aphid biotypes that induced susceptibility to another biotype though.…”
Section: Aphid-induced Plant Genesmentioning
confidence: 82%
“…in barley with monogenic resistance to S. graminum , pre-infestation with a non-compatible aphid biotype led to reduced feeding by a compatible biotype, indicating defense induction by the former (Hays et al, 1999). Similarly, Zytynska et al (2016) found biotype-dependant induction of numerous transcripts and reduction of aphid population growth of S. avenae in barley. In neither of these two barley studies were there aphid biotypes that induced susceptibility to another biotype though.…”
Section: Aphid-induced Plant Genesmentioning
confidence: 82%
“…Since the temperature in the experiment was above the threshold temperature that male aphids are produced, the changes in the relative genotype frequency in aphid population are due to the differentially growth rate of the two clonally reproducing genotypes. Different aphid genotypes induce variable plant defences when feeding, with fitness consequences for other aphid genotypes (Zytynska et al 2016), and these will also vary among plant varieties (Delp et al 2009). Aphids also release salivary proteins into the plant to facilitate feeding and suppress plant defences (Yates & Michel 2018) and it is likely that genetic variation in both the aphid and plant influence the outcome of these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…As aphids feed they induce plant defences, which also vary dependent on the plant (Delp et al . 2009) and aphid genotype (Zytynska et al . 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aphids are sucking insects and feed from the phloem of plants (Harrewijn, Minks, & Mollema, ; Kehr, ). Even though they do not cause as much physical damage as chewing herbivores do, they can have large effects on plants by extracting nutrients and are known to induce defence responses within the plant (Fidantsef, Stout, Thaler, Duffey, & Bostock, ; Voelckel, Weisser, & Baldwin, ; Zytynska, Jourdie, Naseeb, Delneri, & Preziosi, ), including triggering the emission of sesquiterpenes (Bernasconi, Turlings, Ambrosetti, Bassetti, & Dorn, ). Differences between plant genotypes, or between plants of different nutrient status, strongly affect aphid growth (Zytynska & Weisser, ).…”
Section: Introductionmentioning
confidence: 99%